Analyze The Effect of The Impeller Type on Bearing Rating Life - Fatchan Mubarok Tsani; Yasinta Sindy Pramesti (Mekanika)
One of the essential components of a balancing machine is the bearing, which is a crucial component that ensures stability, precision, and efficiency in the balancing process. Although there were high-quality bearings on the market, ongoing research was needed to ensure that balancing machine bearings could supply the specific needs of the industry and continued to improve their reliability and efficiency; the use of bearings specifically designed for balancing applications and of high-quality is necessary to ensure optimal performance and accurate results. This study aims to examine the impact of varying impeller types on balancing machine-bearing life in commercial companies. This research adopts a quantitative causality method, collecting data and samples during the study and then analyzing them using the Analysis of Variance (ANOVA) method. Bearing life is measured using a sum by combining several factors. The results of the research revealed that from ANOVA analysis with an error percentage of 0.05, a significance value of 0.006 was obtained and F = 44.582, Ftable = 9.55, which means calculated F > Ftable so it can be concluded that the type of impeller was affected bearing life.